2017
DOI: 10.3897/phytokeys.80.13338
|View full text |Cite
|
Sign up to set email alerts
|

Macrosolen bidoupensis (Loranthaceae), a new species from Bidoup Nui Ba National Park, southern Vietnam

Abstract: Macrosolen bidoupensis Tagane & V.S.Dang, sp. nov. (Loranthaceae) is newly described from Bidoup Nui Ba National Park in Lam Dong Province, southern Vietnam. The new species is characterized by small broadly elliptic to circular leaves, sessile to short petioles, slightly cordate to rounded leaf bases, 4–5 pairs of lateral veins and a basally green corolla tube. An illustration, a summary of DNA barcoding of the plastid genes rbcL and matK, and a key to the species of Macrosolen in Vietnam are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Critically Endangered (CR). From our intensive field survey in Bidoup-Nui Ba Naitonal Park and its vicinities from 2015 to present (Tagane et al 2017& 2020, Binh et al 2018b, Lithocarpus bidoupensis was found only in a narrow area within the protected areas of Bidoup-Nui Ba National Park, and its adjascent area of Son Thai Commune at the elevation range between 1400 and 1669 m. In the area, 0.6-1.1 cm high, 1.2-1.5 cm in diam., glabrous, reddish brown to grayish brown in sicco, tomentose with soft white hairs near apex; basal scar slightly concave, 1.2-1.4 cm in diam.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Critically Endangered (CR). From our intensive field survey in Bidoup-Nui Ba Naitonal Park and its vicinities from 2015 to present (Tagane et al 2017& 2020, Binh et al 2018b, Lithocarpus bidoupensis was found only in a narrow area within the protected areas of Bidoup-Nui Ba National Park, and its adjascent area of Son Thai Commune at the elevation range between 1400 and 1669 m. In the area, 0.6-1.1 cm high, 1.2-1.5 cm in diam., glabrous, reddish brown to grayish brown in sicco, tomentose with soft white hairs near apex; basal scar slightly concave, 1.2-1.4 cm in diam.…”
mentioning
confidence: 92%
“…1 ) is in the core zone of UNESCO Langbiang Biosphere Reserve, which is in Lam Dong Province in the central highland of Vietnam. The national park, with the area of 70,038 ha covering almost the entire Langbiang Plateau, harbors 1933 species of vascular plants ( Bidoup-Nui Ba National Park 2021 ) including 62 threatened species ( Ban et al 2007 ; IUCN 2012 ), and 42 endemic species ( Tagane et al 2017 , 2020 ; Bidoup-Nui Ba National Park 2021 ). For Fagaceae , 25 species of Lithocarpus , nine species of Castanopsis , eleven species of Quercus , and one species of Trigonobalanus have been recorded from Bidoup-Nui Ba National Park ( Dung 2005 ; Ngoc et al 2016 ; Binh et al 2018a ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Tagane et al [10] described species Macrosolen bidoupensis from Lam Dong province, southern Vietnam. The study also provided the key for seven Macrosolen species in Vietnam including M. bidoupensis.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Seven species were recorded in Viet Nam. [2,3] Macrosolen bidoupensis, a new species was discovered in Bidoup, Nui Ba National Park, Lam Dong Province, Vietnam in 2017. [2] In our earlier research, four triterpenoids, 3-oxofriedelane (1), 3-hydroxyfriedelane (2), 3hydroxyfriedelane-28-oic acid (3), and 3hydroxyglutin-5-ene (4) were verified from this species.…”
Section: Introductionmentioning
confidence: 99%